2015
DOI: 10.1523/jneurosci.0864-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Wave Ripples during Visual Exploration in the Primate Hippocampus

Abstract: Hippocampal sharp-wave ripples (SWRs) are highly synchronous oscillatory field potentials that are thought to facilitate memory consolidation. SWRs typically occur during quiescent states, when neural activity reflecting recent experience is replayed. In rodents, SWRs also occur during brief locomotor pauses in maze exploration, where they appear to support learning during experience. In this study, we detected SWRs that occurred during quiescent states, but also during goal-directed visual exploration in nonh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
122
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(143 citation statements)
references
References 92 publications
14
122
0
Order By: Relevance
“…Moreover, hippocampal ripples are coupled with neocortical spindles in human epilepsy patients 103,173 , as they are in rats 102,108 . In monkey hippocampus, sharp wave-ripples that appear very similar to their counterparts in rodents also occur during inactive and active states 174,175 . Finally, separate slow and fast gamma rhythms may occur in primates, as in rodents.…”
Section: Figurementioning
confidence: 81%
“…Moreover, hippocampal ripples are coupled with neocortical spindles in human epilepsy patients 103,173 , as they are in rats 102,108 . In monkey hippocampus, sharp wave-ripples that appear very similar to their counterparts in rodents also occur during inactive and active states 174,175 . Finally, separate slow and fast gamma rhythms may occur in primates, as in rodents.…”
Section: Figurementioning
confidence: 81%
“…Secondly, the magnitude of myogenic artifacts is modulated across ipsiversive and contraversive saccades, whereas our data do not show a correlation between LFP magnitude and saccade direction. Thirdly, in primates hippocampal LFP polarity reverses along the mediolateral axis (Hoffman et al, ), and possibly not across cellular laminae (Leonard et al, ) as is the case in rodents, a trend found across simultaneously recorded electrode pairs spanning the mediolateral axis (Figure S4). Lastly, regarding possible thalamic contamination, where neurons encode efference copy signals for saccades (Sommer & Wurtz, ), as far as we know these cells do not encode saccade amplitudes in their firing rate.…”
Section: Discussionmentioning
confidence: 98%
“…SWRs are biased to occur during neocortical UP states (Battaglia et al, ; Molle et al, ), which may facilitate both remote replay of HIPP spiking sequences in the neocortex and, ultimately, memory consolidation (Ji and Wilson, ). In primates and humans, the ripple oscillation has a lower frequency range (∌80–130 Hz) than in rodents (Bragin, Engel, Wilson, Fried., & Buzsaki, ; Clemens et al, ; Leonard et al, ; Ramirez‐Villegas, Logothetis, & Besserve, ; Skaggs et al, ). This mechanism could, therefore, explain the fast gamma‐SO coupling we observed in SWS.…”
Section: Discussionmentioning
confidence: 99%